The Analysis of the Harm Caused by Companies Influencing the Spread of Public Crises for Profit in Monopolistic Competitive Markets - Zhang, Lige; Zuo, Qinwen (Journal of Humanities and Social Sciences Studies, 2023)
It is well known that public crises pose a threat to all citizens of an area, including threats to human safety, property damage, social panic, etc. Public crises are sometimes inevitable, but in a monopolistic competitive market, some companies make profits by influencing the spread of public crises. Such behavior sometimes increases the threat of public crises to citizens, expands the scope of public crises, and even creates new public crises. This paper attempts to analyze the relationship between companies and the spread of public crises under the monopolistic competitive market. First is to define the public crisis and the monopolistic competitive market, then discuss how companies affect the spread of the public crisis under the monopoly market competition, what its purpose is, and what kind of impact it will have on citizens. Finally, this paper will propose ways to reduce the harm that companies do to the spread of public crises.